2007
DOI: 10.1063/1.2717145
|View full text |Cite
|
Sign up to set email alerts
|

Well-width-dependent carrier lifetime in AlGaN∕AlGaN quantum wells

Abstract: A set of Al0.35Ga0.65N∕Al0.49Ga0.51N multiple quantum wells (MQWs) with fixed barrier width and well widths varying from 1.65to5.0nm has been grown by metal-organic chemical vapor deposition. Carrier dynamics in the MQWs were studied using time-resolved photoluminescence (PL) spectroscopy and light-induced transient grating (four wave mixing) technique. The authors observed that the lifetime of nonequilibrium carriers (excitons) increases with decreasing well width and interpreted the effect by stronger locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 17 publications
3
15
1
Order By: Relevance
“…The model of strong localization is also consistent with the unusual carrier lifetime dependence on QW width measured in the same samples and reported in Ref. [5], where longer carrier lifetimes were observed in narrower QWs. Such behavior was attributed to stronger localization.…”
Section: Resultssupporting
confidence: 78%
“…The model of strong localization is also consistent with the unusual carrier lifetime dependence on QW width measured in the same samples and reported in Ref. [5], where longer carrier lifetimes were observed in narrower QWs. Such behavior was attributed to stronger localization.…”
Section: Resultssupporting
confidence: 78%
“…2) showed that carrier lifetime was the longest in the thinnest QWs (~2.7 ns at the lowest excitation) and the shortest in the thickest QW (~1.1 ns). These features we attribute to the effect of carrier localization due to well thickness fluctuations in the thin QWs (in our case, for d = 5.5 nm) (a similar effect was observed in AlGaN/AlGaN QWs [10]). Carrier localization prevents carrier migration to nonradiative recombination centers, therefore weaker localization in the thicker wells leads to shorter carriers lifetimes (we assume that the trap density is similar in three structures).…”
Section: Resultssupporting
confidence: 61%
“…As demonstrated for this set of samples in Ref. [14], the carrier lifetime at room temperature increases with decreasing the well width. This is an indication that the dominant origin of the localization is the well width fluctuations.…”
Section: Resultsmentioning
confidence: 81%